2020
DOI: 10.3390/foods9111642
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Aromatic Plants of the Lamiaceae Family in Bread

Abstract: The antifungal effect of aromatic plants (oregano, thyme, and Satureja) in dry form and as essential oils was evaluated in vitro (in potato dextrose agar (PDA)) and in bread against two phytopathogenic fungi found in food (Aspergillusniger and Penicillium). Gas and liquid chromatography were used to analyze essential oils attained by hydrodistillation of the aerial parts of the aromatic plants and of the dried plant aqueous solutions that were autoclaved for 20 min at 121 °C before analysis. Carvacrol, α-pinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…Results showed that the addition of essential oils had significant effect ( p < 0.05) on decreasing their colony surface area. Thus, oregano ( O. vulgare ), thyme ( Thymus capitatus ), and pink savory ( S. thymbra ) can be incorporated into bread recipes and be used in the food industry, as they have antimicrobial properties [ 147 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Results showed that the addition of essential oils had significant effect ( p < 0.05) on decreasing their colony surface area. Thus, oregano ( O. vulgare ), thyme ( Thymus capitatus ), and pink savory ( S. thymbra ) can be incorporated into bread recipes and be used in the food industry, as they have antimicrobial properties [ 147 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…strains was delayed by 3 days when a whole wheat sourdough inoculated with selected strains of L. plantarum was used [56]. The same effect was observed when 30% (w/w) of a commercial sourdough was used [80] or essential oils from aromatic plants [81], respectively, when a mixture of eugenol-citral was added to the wheat bread doughs [82].…”
Section: As Displayed In Tablementioning
confidence: 72%
“…EOs can be applied as ingredients in the bread formulation, as additives in the packaging or in combination with other technologies (hurdle technology) to prolong the product shelf-life. Recently, Skendi et al [28] tested the effect of three aromatic plants belonging to the Lamiaceae family (oregano, thyme, and Satureja) as EOs or in dry form directly in the bread formulation. According to our results, the authors detected carvacrol, α-pinene, p-cymene, and γ-terpinene as main components and observed that both forms of addition (essential oil and dry material) resulted in a higher efficacy against the Penicillium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the species belonging to the family are aromatic and possess essential oils (EOs) making them valuable in cosmetics, perfumery, food, agriculture, and medicine [24,25]. The use of Lamiaceae species as antimicrobial agents for bread and bakery products preservation has also been reported [7,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%